Implementation and initial outcomes of a spinal cord injury home care program at a large veterans affairs medical center. (4th March 2019) - Sippel, Jennifer L.; Bozeman, Sara M.; Bradshaw, Ledjona; Cipher, Daisha J.; McCarthy, Michael; Wickremasinghe, Itala M.
Abstract : Objectives: Describe an interdisciplinary spinal cord injury home care program (SCIHCP), sample demographics for the veteran participants, and initial impact of SCIHCP on health care utilization and mortality. Design: Retrospective review. Setting: SCIHCP of the Spinal Cord Injury Center, VA North Texas Health Care System (VANTHCS). Participants: Patients with SCI/D enrolled in the SCIHCP during January 6, 2006 through January 9, 2012, whose injury occurred at least one year prior to enrollment(n = 125). Main Outcome Measures: VANTHCS hospital admissions, length of stay (LOS), and emergency department (ED) visits evaluated one year before and one year after SCIHCP enrollment; mortality evaluated one-year post-enrollment. Results: There were no significant changes in number of ED visits, number of hospital admissions, or LOS over time. More home care visits and more mental health comorbidities predicted more hospital admissions. Older patients and those with more mental health comorbidities were more likely to experience increases in LOS. These prediction models were significant after adjusting for injury level, age, race, time since SCI, and number of medical comorbidities. More home care visits were associated with lower likelihood of mortality post-enrollment. Conclusions: Inpatient and ED utilization did not change one year after enrollment, but more SCIHCP visits predicted more hospital admissions and lower likelihood of mortality in the post-evaluation year. The support, education, and care continuity SCIHCP generates might be related to increased inpatient access and lower mortality rate. Veterans with increased mental health comorbidities used inpatient services more, and might need additional support.